HUBUNGAN PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI DI MALUKU PADA MASA PANDEMI COVID-19 - Palijama, Arnelia (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2021)
The economic development of a region aims to obtain high economic growth, which can encourage an increase in the income per capita of the population followed by an increase in human development. The purpose of this study was to determine the effect of economic growth on human development performance in Maluku Province during the Covid-19 pandemic period. The research uses a quantitative approach with descriptive and inferential analysis methods. Simple linear regression analysis technique was applied to determine the relationship between HDI and economic growth and mapped it on a quadrant map. The findings obtained illustrate that the HDI growth in Maluku in 2020 slowed to 0.06 percent, while economic growth contracted to 0.92 percent. There are no districts/cities whose HDI and economic growth are lower than the Maluku Province figure. Around 81 percent of districts/cities are mapped in Quadrant II (lower HDI and higher economic growth than the Maluku figure). The estimation results of the regression equation confirm a very strong relationship. The results of the study indicate that the Covid-19 pandemic has an impact on the slowdown in the HDI growth of Maluku Province in 2020.